UZBEKISTAN IN THE CONDITIONS OF TRIGONELLA FOENUM-GRAECUM L. (EKOFOROMASI PAKISTAN) WHICH MORPHOLOGICAL ANALYSIS OF SEEDS - Mardonov Fozilbek Mardon ugli; Qaysarov Vahob Tukhtamishevich; Ubaydullaev Farkhod Bakhtiyarullaevich (Journals Park Publishing, 2025)
This research T. foenum-graecum (Greek shambalasi) morphological features of the plant was conducted in the conditions of uzbekistan, made a deep analysis on the basis of experimental studies. Research for T. foenum-graecum seed plant which study morphological indicators, and identified specific biological features biomorfologik. In particular, the weight of 1000 pieces hawthorn seeds 15,4-15,7 g, determines that it is around. In terms of appearance the seeds of his size and highlights. Their length 5-6 mm and 2-3 mm in width, have them in brown or dark brown color, pink colored seed hawthorn seems to be on the end of a sign. Also, half the seeds in the form of black dots on the basis of the presence of oysimon, was dedicated as foreign to the specific characteristics of its. Morphological indicators and provides accurate information about their research, which image of the seeds of this plant allows us to form a more complete picture about the features of specific biomorfologik more. The results of this research, T. foenum-graecum plant in uzbekistan in the context of the development of morphological changes and be applied in practice gives important knowledge about its. These changes of the plant, agricultural and effective to be applied in the pharmaceutical industry is of great importance. Practical importance of research results in the planting of plants, their growth will help to control and use resources effectively.
Keywords: Medicinal herbs, seeds, unuvchanlik, Trigonella, biomorfologiya, biomass, temperature, planting, growth, optimal, seed size, burmali shell.